Developing a Digital Handout for Assessment in Science Course: An ADDIE Model Approach - Ai Nurlaelasari Rusmana; Lilit Rusyati; Vika Marsya Ramadhani; Indhira Ayu Sevyani; Diki Nur Afriyansyah (Universitas Garut, 2026)
Assessment literacy is a fundamental competency for preservice teachers, yet the Assessment in Science course still lacked structured learning materials that could support both classroom learning and independent study. This study aimed to develop a digital handout for the course and examine its practicality based on students’ evaluations. This study employed a Research and Development design using the ADDIE model, which involved the phases of Analysis, Design, Development, Implementation, and Evaluation. Participants included 28 undergraduate science education students as target users, three students for readability testing, and one science education and assessment expert for qualitative validation. Data were collected through questionnaires consisting of Likert scale items and open-ended questions. The data were further analyzed using descriptive statistics and thematic analysis. The development process produced a digital handout containing learning objectives, concise theoretical explanations, practical examples, summaries, self-assessment questions, and interactive multimedia elements such as hyperlinks and QR codes. The practicality evaluation showed that the handout was rated practical overall (M = 4.17; SD = 0.82), with its strongest contributions in supporting concept understanding, classroom learning, and future review, although improvements are still needed in visual quality and layout spacing. In conclusion, the digital handout can be a practical learning resource for the Assessment in Science course. The findings imply that systematically developed digital materials can support assessment literacy in preservice science teacher education.Keywords: ADDIE model, assessment literacy, digital handout, preservice science teacher, science teacher education